A Long Preoperative Duration of Symptoms Is Associated With Worse Functional Outcomes After 1-Stage Arthroscopic Treatment of Rotator Cuff Tears With Shoulder Stiffness. (August 2017) - Chen, Yuzhou; Chen, Shiyi; Qiao, Yang; Ge, Yunshen; Li, Hong; Chen, Jiwu; Hua, Yinghui; Li, Yunxia
Background: Rotator cuff tears with shoulder stiffness remain a difficult issue. Despite the reported satisfactory results of 1-stage surgery, little information is available regarding the factors that affect clinical outcomes. Purpose/Hypothesis: To evaluate the 1-stage arthroscopic treatment of rotator cuff tears with shoulder stiffness and to present the influence of duration of symptoms (DOS) on postoperative functional outcomes. The hypothesis was that a long preoperative DOS is related to worse functional outcomes. Hypothesis: A long preoperative DOS is related to worse functional outcomes. Study Design: Cohort study; Level of evidence, 2. Methods: A cohort study was performed with consecutive patients who underwent 1-stage surgery between January 2012 and July 2014. Forty-four patients were enrolled in the long DOS group (DOS ≥6 months or LDOS), and 38 were enrolled in the short DOS group (DOS <6 months or SDOS). There were no significant differences in the other variables between the groups. The patients were followed for a mean of 33.8 months, and the functional and radiographic outcomes were compared. Results: Both groups achieved apparent functional postoperative improvements in terms of range of motion, pain, strength, and functional scores ( P < .001 for all). Despite the overall improvements, the patients in the SDOS group had significantly better outcomes according to all functional instruments. The mean postoperative abduction and external rotation at the side in the SDOS group were higher than in the LDOS group (abduction: 162.2° vs 152.8°, respectively [ P = .002]; external rotation: 64.7° vs 56.9°, respectively [ P = .004]). The mean postoperative functional scores in the SDOS group were all higher than in the LDOS group (American Shoulder and Elbow Surgeons [ASES] score: 91.1 vs 81.9, respectively; Constant-Murley score: 76.9 vs 71.8, respectively; Fudan University Shoulder Score [FUSS], 90.6 vs 81.1, respectively), and the mean postoperative visual analog scale (VAS) score for pain in the SDOS group was lower (0.7 vs 1.8, respectively) ( P < .001 for all). The difference in the retear rates was not significant, with 7 retears in the SDOS group and 4 in the LDOS group ( P = .216). Conclusion: One-stage surgery effectively achieved overall improvements. A preoperative DOS of ≥6 months led to poorer functional outcomes, which suggests that surgeons should propose a surgical treatment for this condition before symptoms persist for 6 months.